Analisis Bauran Promosi dalam Meningkatkan Minat Beli Pada Toko Kue Enggal Jaya Group - Rahma Alya Adi Putri; Ady Tia Ramadhan (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the implementation of the promotional mix to increase consumer purchasing interest at Enggal Jaya Group Cake Shop located in Baleendah, Bandung Regency. Amidst increasingly fierce competition in the culinary business, the success of a business is largely determined by the ability to implement appropriate marketing strategies, particularly in the promotional aspect. A good promotional strategy can attract consumer attention, build loyalty, and ultimately increase sales volume and expand market share. This study uses a qualitative descriptive approach with data collection methods through direct field observation, in-depth interviews with the owner and marketing staff, and documentation of promotional activities that have been carried out. The main focus of the study is directed at six elements in the promotional mix: advertising, sales promotion, personal selling, public relations, direct marketing, and digital marketing. The results show that Enggal Jaya Group Cake Shop has not yet optimized the use of the promotional mix comprehensively. Promotion is still dominated by conventional methods such as word of mouth and direct discounts to consumers in the store. Meanwhile, the use of social media such as Instagram, Facebook, TikTok, and WhatsApp Business is still very limited. In fact, this media has great potential to reach a wider consumer base, especially millennials and Gen Z, who tend to be digitally active. Therefore, this study recommends that Toko Kue Enggal Jaya Group develop a more integrated and adaptive promotional strategy to the development of information technology. Strengthening brand image through engaging visual content on social media, collaborating with local food influencers, and implementing a digital-based customer loyalty program can be effective solutions to increase business visibility, strengthen customer relationships, and encourage sustainable consumer purchasing interest.